Marxism, Culture and the Measurement of Value - James McMahon (Forum on Capital As Power - Toward a New Cosmology of Capitalism, 2015)
Various studies of mass culture use the Marxist labour theory of value to conceptualize how capital is being accumulated from cultural production and its broader social and immaterial dimensions. However, there is a significant methodological problem that lingers. The issue stems from the concept of economics and, more technically, the definition of capital. If economic value is conceptualized as a magnitude of productivity, theorists must follow through on a series of steps, both logical and empirical. Unfortunately, this basic assumption about the nature of capital creates an array of problems for the theorist that is interested to know, in more concrete detail, how the social relations of culture are theoretically relevant to capital accumulation. Essentially, there is no solid ground for Marxism, of various sorts, to claim that socially necessary abstract labour time is the essence behind the heterogeneous appearances of commodities, prices and profit. And as this paper demonstrates, this problem affects theories that are using Marxism to explain the economic value of artistry, creativity, advertising, consumer desire and other aspects of culture. Moreover, since the problem goes to the roots of the Marxist method, theoretical dilemmas about the labour theory of value precede any subsequent modification to the definitions of labour and productivity in cultural activity.
Keywords: 330; labour theory of value; Marxism; mass culture